COMBATING CHILD LABOUR - A SOUTH AFRICAN CHALLENGE - D L (Vasintha) Veeran (Social Work/Maatskaplike Werk, 2003)
Until recently child labour in South Africa received little attention from government and non-governmental organisations (NGOs). This lack of recognition is evidenced by the dearth of research and comprehensive statistics on the extent of the problem. Although statistics have been forthcoming from the International Labour Organisation (ILO) and United Nations Children’s Education Fund (UNICEF), they differ significantly on the estimates of the magnitude of child labour. The ILO estimated in 1996 that there were 120 million full-time working children ranging from 5 to 14 years. This figure is doubled when part-time working children are taken into consideration. The distribution of child labour indicates that this phenomenon is located primarily in developing countries, viz. Asia 61%, Africa 32% and Latin America 17% (Grootaert & Patrinos, 1999). Nevertheless, the highest proportion of child workers in relation to the total population is in Africa (Fyfe, 1989). Compared against global estimates, child labour in South Africa has been underestimated, contributing largely to the low-priority status it is accorded. According to the Labour Directorate there were about 200 000 children working in South Africa in 1997 (Department of Labour, 1998), some as young as 5 years. Without conclusive research into the problem of child labour, it can be argued that this figure is a conservative estimate as a large percentage of “unseen” child labour is not accounted for. This includes unpaid domestic work and work in the informal sector. Other related activities that are neglected in the estimation are the increasing number of child prostitutes, largely as the result of the increasing number of street children.